Inovação gerencial em organizações híbridas: o caso do registro de preços no SESC PR - Tonet, Ernandes (2016)
Innovation constitutes a fundamental precept for organizations’ survival in an increasingly competitive and changing market. Innovation is present in every kind of organization and is widespread in companies in different forms and concepts. In order to understand how innovation happens in unconventional organizations, also known as hybrid organizations, this study aimed at checking the development of the implementation process of a price registration system at Sesc PR. The price registration system, which is studied in hybrid organizations, is also understood as public organizations’ management process of purchasing and contracting. The objective of this research is to understand how this system was implemented within the period from 2006 to 2015 in the Social Service of Commerce from Paraná State (Sesc PR). For the qualitative approach we used the case study method, interviewing some of the institutions’ directors and advisors and also an external consultant. Regarding the qualitative approach, documents related to price registration system and historical documents of the institution were analyzed. Four interviews were performed with members of the organization and one was done with an external consultant who had belonged to the institution’s staff. These people took part in the implementation process of the price registration system at Sesc PR. These interviews were analyzed along with the historical documents and the implementation of the process mentioned above was verified. Since there aren’t enough literature resources on the subject of hybrid organizations, the theoretical foundation was based on the management innovation and social phenomena of the organizations and their origins. Through qualitative analysis results, one found that the management innovation process at Sesc PR does not follow the logic of the private sector and is also distinct from the processes used in its innovation process, ruled by rival demands in terms of legitimacy. On the one hand, the sponsoring unions seek to strengthen the private nature of the organization and keep it away from the public logic, pressing them for the adoption of market practices and for efficient management of resources. On the other hand, Sesc is influenced by State control bodies, which pushes the institution to adopt legitimate practices and standards within public companies and become favorable to auditing and external inspection. The resultant of these forces characterizes the organization’s hybrid management. In their efforts to legitimize practices and work with the unions and beneficiaries of the organization’s services, the innovations at Sesc PR aim at minimizing the direct external control through legal actions in defense of the private nature and the organization’s autonomy by establishing regulations and their own procedures to replace the rules of conduct imposed by inspection agencies. However, the loss of legitimacy with these public inspection agencies can be harmful to the organization, since it is politically fragile to the extent that its performance depends on the resources transferred by the State. Thus, instead of adopting a management method exclusively guided by the market, it employs a conciliatory strategy of innovation, making concessions regarding the form and content of innovations. Management hybridity manifests itself in a management innovation strategy through the isomorphism to public management practices. Although the direct intervention of State bodies is rejected, the regulations they create, their standards and business management practices are the main source of inspiration for the creation of internal regulations and for the change of management practices. The management innovation at Sesc PR’s purchasing process is characterized therefore as a strategic effort for maintaining the organization’s legitimacy and its practices based on the ambiguous guidelines from the two major axes of the organizational hybridity instead of seeking operational efficiency according to the market logic or symbolic legitimacy in the face of public inspection pressure. Thus, one can verify that the organizational response to different institutional pressures was not manifested as a simple technical and institutional uncoupling. Instead, the organization engaged its practices to different institutional guidelines through the separation of image and representation performance levels from the rules and actions, keeping legitimate in its hybridity, although far from efficiency ideals from both public and private sectors.